Neuromotor dynamics of human locomotion in challenging settings - Santuz, Alessandro; Brüll, Leon; Ekizos, Antonis; Schroll, Arno; Eckardt, Nils; Kibele, Armin; Schwenk, Michael; Arampatzis, Adamantios (iScience, 2020)
Is the control of movement less stable when we walk or run in challenging settings? Intuitively, one might answer that it is, given that challenging locomotion externally (e.g., rough terrain) or internally (e.g., age-related impairments) makes our movements more unstable. Here, we investigated how young and old humans synergistically activate muscles during locomotion when different perturbation levels are introduced. Of these control signals, called muscle synergies, we analyzed the local stability and the complexity (or irregularity) over time.
Available online 24 December 2019
Gesehen am 03.04.2020